Vascular Morphology has No Direct Relationship with Atherosclerotic Plaque Burden in Patients with Symptomatic Middle Cerebral Artery Stenosis - Liu, Lu; Huo, Chengju; Sun, Hao; Yang, Hua; Zhang, Rui; Wang, Lexin; Xia, Zhangyong (Current Neurovascular Research, 2019)
Background: The vascular morphology and the characteristics of atherosclerotic plaques in the middle cerebral artery (MCA) have not been fully studied with high-resolution magnetic resonance imaging (HR-MRI). Objective: HR-MRI was applied to investigate vascular morphology and atherosclerotic plaque in patients with symptomatic MCA stenosis. Materials and Methods: A total of 343 patients with symptomatic MCA stenosis were enrolled in this study. All the patients were examined by HR-MRI to analyze the morphology of MCA and the M1 segment (MCA-M1), the characteristics and the location of the plaques. Results: The proportion of L-shaped MCA-M1 decreased, while the proportion of S-shaped MCAM1 increased with age. The anterior plaques were the most common in all the patients. The superior plaques were relatively common in patients with L-shaped and U-shaped MCA-M1, while the inferior plaques were relatively common in patients with inverted U-shaped and S-shaped MCAM1. Among all the plaques, the majority were isointense or heterogeneous. The MCA-M1 morphology had no direct relationship with the common risk factors of atherosclerosis and the clinical outcomes of the patients after 12 months of follow up. Conclusion: The morphology of MCA-M1 is not directly related to the plaque burden or the degree of stenosis in patients with symptomatic MCA stenosis. The morphology of MCA-M1 is not associated with the risk factors of atherosclerosis, or the clinical outcomes of the patients.
Keywords: stroke